Hypoxic MSCs Secretome Modulates IL-18-Mediated Inflammatory in Type 2 Diabetes Mellitus via AP-1 Regulation - Amansyah, Fajar; Alif, Iffan; Irawan, Risky Candra Satria (International Journal of Cell and Biomedical Science, 2024)
Background: Chronic inflammation is central to the pathophysiology of Type 2 Diabetes Mellitus (T2DM), contributing to the progression of metabolic dysfunction characterized by hyperglycaemia and insulin resistance. This study aims to investigate the therapeutic potential of the hypoxic MSCs secretome (SH-MSCs) in reducing inflammation of a T2DM rat model. Methods: T2DM was induced in Wistar rats through a high-fat diet (HFD) followed by streptozotocin (STZ) administration. A total of 24 healthy male Wistar rats were randomly assigned to five groups: healthy control, T2DM, T2DM + metformin, T2DM + SH-MSCs. Results: SH-MSCs significantly reduced IL-18 mRNA expression, a key indicator of proinflammation, and suppressed the expression of AP-1 mRNA, a crucial proinflammatory transcription factor. Conclusion: These findings highlight the therapeutic potential of SH-MSCs as an alternative approach to alleviate inflammation in T2DM.